2014
DOI: 10.12691/ajcmr-2-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Stress Induces By Malaria Parasite Infection and Effect of Anti-malaria Drugs on Stress Index, Lipid Profile in Uncomplicated Acute Malaria Infected Adult Individuals

Abstract: Malaria infection is accompanied by increased production of reactive oxygen species which indicates the environment for oxidative stress. Oxidative stress in malaria may originate from several sources including intracellular parasitized erythrocytes and extra-erythrocytes as a result of haemolysis and host response. The aim of this study is to estimate level of stress induces by malaria parasite infection and effect of anti malaria drugs on stress index in uncomplicated acute malaria infected adult individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…Though, serum SOD activity and PCO level were altered in children with severe malaria in this study, corroborating some earlier reports [53,50,54], the association between severe malaria and PCO/SOD, and HCO3/glucose ratios has not been reported in previous literatures to the best of our knowledge and all these parameters exhibited relatively low sensitivity with relatively high specificity or vice versa (Table 3 and Figure 1). This suggests that these parameters may not be effective malaria diagnostic parameters.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Though, serum SOD activity and PCO level were altered in children with severe malaria in this study, corroborating some earlier reports [53,50,54], the association between severe malaria and PCO/SOD, and HCO3/glucose ratios has not been reported in previous literatures to the best of our knowledge and all these parameters exhibited relatively low sensitivity with relatively high specificity or vice versa (Table 3 and Figure 1). This suggests that these parameters may not be effective malaria diagnostic parameters.…”
Section: Discussionsupporting
confidence: 92%
“…In severe malaria, there is parasite induced oxidative stress which depletes some components of the antioxidant system; this leads to increased oxidation of biomolecules such as protein, thus causing an elevation in serum PCO level [50] with a decrease in the serum antioxidant (SOD), thus overwhelming the first line enzymic antioxidant defense in an attempt by the host to offset the effect of the increasing oxidative stress [51][52]. This study revealed normal serum bicarbonate level compared to control and it followed no regular pattern with increase in parasite density (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%